Digital economy and high-quality development of the healthcare industry - Zijing Ding; Xinyue Qu; Chen Li (Frontiers Media S.A., 2024)
The high-quality development of the healthcare industry is of great significance for improving people's health and promoting the construction of a harmonious society. This paper focuses on the relationship between the development of China's digital economy and the high-quality development of the healthcare industry. Based on the panel data of 30 provinces in China from 2011 to 2020, this paper empirically studies whether the development of the digital economy promotes the high-quality development of the healthcare industry. This study finds that the development of digital economy has significantly promoted the high-quality development of the medical and health industry. The results of this study are still valid after a series of robustness tests including variable substitution, sample adjustment, and endogenous problem mitigation. Heterogeneity analysis shows that the effect of this policy is more significant in the eastern region and southern areas. The results of spatial econometric analysis show that the development of digital economy has obvious spatial spillover effect. The research in this paper can provide reference for developing countries to enhance the development level of digital health industry and improve people's lives.